Digital marketing techniques for promotion of "Infrastructure of Serbian Railways" - Stojanović, Danijela; Stanisavljević, Nenad; Jovičić, Elena (E-business technologies conference proceedings, 2021)
This paper explores and analyses the presentation of "Infrastructure of Serbian Railways", a state-owned railway company, on the Internet and social media in 2020, as well as the effects achieved in the media and the public. The aim of the research is to determine the extent to which the business of "Infrastructure of Serbian Railways" can be presented on the Internet and social media by company’s activities and shared information.